Mine Dewatering Design for Re‑Mining in a Mined‑Out Laterite Nickel Pit: Case Study of South Pit, PT NPM, Central Sulawesi, Indonesia - Ananda, Sri Sovia Duha; Baharuddin, Ichsan Invanni; Har, Rusli; Prabowo, Heri (UIR PRESS, 2026)
This study aims to design an effective mine dewatering system for the South Pit mined-out area of PT Nusajaya Persadatama Mandiri, supporting re-mining activities. The methods used include hydrological analysis to determine the design rainfall using the Log Pearson Type III distribution, calculation of rainfall intensity using the Mononobe method, and estimation of runoff discharge using the rational method based on the catchment area. The results show that the design rainfall is 72.2 mm/day with a rainfall intensity of 49.9 mm/hr and a catchment area of 13.47 ha. The total inflow into the pit is 0.48 m³/s (1,726 .20 m³/hr), requiring a sump capacity of 7,250.03 m³. The pumping system is designed using a DnD LCC-M 100 pump with a capacity of 300 m³/hr, operated for 14 hours/day. The pumped water is conveyed through a 6-inch diameter HDPE pipe to a trapezoidal open channel, where it is then discharged into a Water Management Pond (WMP) with a total capacity of 11,200 m³, consisting of four compartments. The research results indicate that the designed mine drainage system is capable of effectively controlling mine water, thereby supporting safe and efficient re-mining operations.